2006
DOI: 10.1177/1479972306070371
|View full text |Cite
|
Sign up to set email alerts
|

Use of a chronic disease management programme in COPD to reduce hospital admissions

Abstract: Chronic obstructive pulmonary disease (COPD) accounts for a large number of hospital admissions and numerous interventions have attempted to reduce exacerbations requiring hospitalization. This paper describes the implementation of a community based COPD management programme led by a respiratory physiotherapist to improve home management of COPD and its effect on reducing readmissions and/or length of stay in hospital. One-hundred and twenty-five patients (median age 73) referred with COPD exacerbations met th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Our study is short term compared to the long-term study conducted by Pearson et al (2006) and included only patients with advanced COPD. Pushparajah, McClellan, Henry, and Kuitert (2006) showed a signifi cant reduction in both length of stay and total hospitalization in more severely ill patients by implementation of a chronic disease management program similar to ours. A self-management program as part of an overall supported package of care has been shown to reduce readmission rates (Gadoury et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
“…Our study is short term compared to the long-term study conducted by Pearson et al (2006) and included only patients with advanced COPD. Pushparajah, McClellan, Henry, and Kuitert (2006) showed a signifi cant reduction in both length of stay and total hospitalization in more severely ill patients by implementation of a chronic disease management program similar to ours. A self-management program as part of an overall supported package of care has been shown to reduce readmission rates (Gadoury et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
“…Strong clinical leadership within collaborative quality improvement programmes 275 and individual specialist provision of care, 271 both improved process outcomes in these before-and-after studies, but neither study provided evidence of clinical effectiveness.…”
Section: Implementing National Programmesmentioning
confidence: 99%
“…248,257,260,262,273,276 l Technological solutions (such as cCBT programmes, automated telephone calls) are being explored and show some promise. 225,238,265,267,269,271 l The only study which specifically explored duration of intervention and effect found evidence of benefit as much as 5 years after a one-off intensive insulin training course. 243 Intensive courses in diabetes and LBP seem to be more effective than less intensive programmes.…”
Section: Implementation Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations